The Role of Information and Communication Technology in Vocational and Technical Education in Nigeria - Tsado, Elijah (Richtmann Publishing, 2012)
This paper attempts to examine the roles of Information Communication and Technology (ICT) inVocational and Technical Education (VTE) in Nigeria. To achieve this, the definitions of ICT and VTE weregiven. The benefits of ICT and the use of ICT were also discussed. The challenges of VTE were alsohighlighted before the exposition on the role of ICT in VTE. It was concluded that the emergence of ICTremain at the centre of global socioeconomic transformation. The paper recommended that schoolsoffering VTE should be connected to ICT facilities and the staff should be properly trained to be ICTcompliant.